Improving the dynamic stability of electrical power systems via vibration damper that relies on integrating controloptimised with an advanced operational amplifier - Khwther Abbodd Neamah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this research is to improve the dynamic stability of electric power systems by introducingadditional damping to the excitationcontrol circuit by means of a vibration damper that relies on integrating the signal provided by an advanced operational amplifier circuit with a negative feedback signal obtained from solving the Riccati equation. This control signal represents different ratios of state variables of the system.To test its effectiveness, the proposed method was applied to a machine-made electrical power systemsynchronouslyconnected to an infinite collector rod viaa power transmission line.The mathematical model is built. The linearity of the power system of degree Thefol the time response of state variables to this was stud the system. This study confirmed that the proposed method generatesufficient negative damping to improve system stability by reducing the vibrations arising from disturbances.